Assertiveness and its relationship to excessive use of the internet among secondary school students - Aljabr, Bashaiyr Abdullah; Hussein, Abdulaziz mohammed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to explore the relationship between self-assertion and the excessive use of the internet among secondary school students. It also intended to explore gender differences in self-assertion, the excessive use of the internet, and the preferred internet material. Participants were (500) secondary school students, (250 males and 250 females). Their ages of the sample ranged from 15 to 19 years. They were in the first semester of the academic year 1438-1439H.The descriptive method (correlational) was used in the study. Data were collected using the Self-assertion Scale developed by Ghareeb (1995), and the Internet Addiction Scale developed by Al-Qarni (2011). Results revealed a statistically significant negative correlation between self-assertiveness and the excessive use of the internet The degree of correlation with the Pearson coefficient was (828-). In addition, there were no gender differences found in the excessive use of the internet. The results also revealed significant gender differences in types of internet contents that attract the two sexes. Females were found to be more attracted to reading activities than were males. Conversely, males were more attracted to WhatsApp and other applications than were females. Finally, the study presented a number of recommendations and suggestions for further research.
Keywords: assertiveness; excessive use of the internet; addiction to the internet